ROOT AND MORPHOLOGICAL CHARACTERISTICS OF EUCALYPTUS SEEDLINGS PRODUCED IN BIODEGRADABLE CONTAINERS - Santos, Renan Alves; Novaes, Adalberto Brito de; Sousa, Nilton José (Floresta, 2024)
The objective of this study was to evaluate the nursery and field development of eucalyptus seedlings produced in biodegradable containers (BC), based on morphological and root characteristics, compared to the conventional method in 55-cm³ tubes. The experiment was conducted in a completely randomized experimental design, using a 3×2 factorial arrangement consisting of three types of containers (55-cm³ tubes; 76-cm³ BC; and 115-cm³ BC) and two eucalyptus clones (CO-1407 and AEC-144). The parameters evaluated in the nursery were: shoot height (SH); stem base diameter (SBD); SH-to-SBD ratio; shoot, root, and total fresh and dry weights; and total number of roots. The parameters evaluated in the field were: SH; SBD; and root distribution. Considering the evaluated characteristics, the use of 115-cm³ BC enabled the development of high-quality seedlings in all evaluation phases. BC-produced seedlings presented better quality and performance in the field. Seedlings produced in 55-cm³ tubes presented lower values for all morphological parameters evaluated in the nursery, as well as in the field up to 120 days after planting.